141 THE EFFECT OF POST-TRAUMATIC STRESS AND POST-TRAUMATIC GROWTH ON HEALTH-RELATED QUALITY OF LIFE IN ADULT CHILDHOOD CANCER SURVIVORS. (1st January 2006) - Casillas, J.; Zebrack, B.; Sanchez, D.; Zeltzer, L. K.
Abstract : Introduction: Two-thirds of childhood cancer survivors are experiencing at least one significant physical or psychosocial late effect, yet they rate their health-related quality of life (HRQOL) as very good. Purpose: To explore factors indicative of post-traumatic stress and post-traumatic growth and their correlation as an explanatory model for reports of good HRQOL. Methods: Cross-sectional design using a convenience sample of 57 childhood cancer survivors who were 18 years of age or older, ≥ 5 years from diagnosis, any malignancy diagnoses ≤ 21 years of age, English or Spanish speaking. Quantitative measures: Impact of Event Scale-Revised (IES-R) and post-traumatic growth inventory (PTGI). Qualitative methods: focus group or individual semi-structured interview was completed. Descriptive statistics and regression models were completed. Semi-structured interviews were audiotaped from which exemplary quotes were abstracted. Results: 18% of the survivors were found to have clinically significant post-traumatic stress symptoms as measured by the IES-R. 84% of the survivors had significant growth. The IES-R total score was positively correlated with new possibilities ( ;gr = 0.26, p = .05) and appreciation of life ( ;gr = .32, p < .05) PTGI subscales. There were positive correlations between the IES-R intrusion and PTGI appreciation of life subscales (;gr = .26, p = .05), the IES-R avoidance and PTGI appreciation of life subscales (;gr = .27, p = .05), and the IES-R hyperarousal and PTGI new possibilities subscales (;gr = .31, p < .05). Qualitative analysis provided further insight into the quantitative findings. "I'm a better person. I see things differently… My whole outlook on life has changed." Conclusions: Although there may be negative psychological consequences of cancer during childhood, as manifested by post-traumatic symptoms, they can coexist with positive psychological effects in adulthood, which may explain, in part, the overall good quality of life of childhood cancer survivors even in the setting of having significant late effects.